2003
DOI: 10.1634/theoncologist.8-5-425
|View full text |Cite
|
Sign up to set email alerts
|

Chemoembolization in the Management of Liver Tumors

Abstract: The dual vascular supply of the liver affords a unique opportunity to explore intraarterial therapies for hepatic malignancies. Chemoembolization is a well-established technique combining intra-arterial chemotherapy with delivery of embolic agents in order to achieve an antitumor effect due to a high local concentration and prolonged dwell time of the drug, along with select ischemia. Many tumors, such as hepatocellular carcinoma, colorectal cancer, and neuroendocrine tumors, cause symptoms and death by local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
0
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(47 citation statements)
references
References 101 publications
0
40
0
7
Order By: Relevance
“…5,6,22,23 Surgical hepatic resection of the tumor is the best therapeutic method, and the only generally accepted and potentially curative treatment for patients with CCC in the absence of primary sclerosing cholangitis, however only a small percentage of patients are candidates for curative surgery because of the advanced clinical stage at the time of diagnosis. 14,24,25 Surgical resection showed a median survival time of 13-44 months (26)(27)(28), and a 5-year survival rate of about 4.1-43%. [26][27][28][29][30] For most of the patients, palliative therapeutic options exist and are based on multimodal promising combinations including systemic chemotherapy, endoscopic biliary stenting, radiation therapy and photodynamic treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6,22,23 Surgical hepatic resection of the tumor is the best therapeutic method, and the only generally accepted and potentially curative treatment for patients with CCC in the absence of primary sclerosing cholangitis, however only a small percentage of patients are candidates for curative surgery because of the advanced clinical stage at the time of diagnosis. 14,24,25 Surgical resection showed a median survival time of 13-44 months (26)(27)(28), and a 5-year survival rate of about 4.1-43%. [26][27][28][29][30] For most of the patients, palliative therapeutic options exist and are based on multimodal promising combinations including systemic chemotherapy, endoscopic biliary stenting, radiation therapy and photodynamic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of TACE has been used in the management of patients with liver metastases from colorectal cancer, breast carcinoma as well as patients with unresectable hepatocellular carcinoma (HCC). [12][13][14][15][16][17] Regarding unresectable CCC there are few studies addressing this issue, and the number of patients on the existing studies is relatively small. Another problem is that there are no studies about patients who were treated with Mitomycin C, Gemcitabine, Cisplatin or with a combination of them.…”
mentioning
confidence: 99%
“…22 The method presented here offers real promise to strengthen the application of TAE for unresectable liver cancers by combining it with antiangiogenic therapy when it is under pressure and suspicion due to some disappointing clinical results. [22][23][24][25] Although the effects of TAE on tumor shrinkage is certain, its efficacy in prolonging survival in HCC patients is controversial, as some studies have shown TAE improves survival of patients, [26][27][28] while a few randomized trials failed to do so. [29][30][31] The present study has demonstrated that TAE led to necrosis of liver tumors and reduced their sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Selective catheter-directed IAC is a standard treatment for HCC confined to the liver but that is not amenable to surgery, which is the situation in up to 75% of new cases worldwide [2,3]. IAC-like approaches such as chemoembolization have demonstrated survival benefits in randomized controlled clinical trials [4] potentially due to improved tumor dose profile.…”
Section: Introductionmentioning
confidence: 99%